Effect of protein and lipid variation in diets for Macrobrachium tenellum, with respect to reproductive indicators - Peña-Almaraz, Omar Alejandro; Vega-Villasante, Fernando; Espinosa-Magaña, Alí Francisco; Guerrero-Galván, Saúl Rogelio; Vargas-Ceballos, Manuel Alejandro (Ecosistemas y Recursos Agropecuarios, 2023)
This work aimed to determine the gonadal maturation, egg and larval quality of Macrobrachium tenellum females fed diets with different protein and lipid levels, using morphological indicators and stress tests. M. tenellum broodstock were captured in the Ameca River, Jalisco-Nayarit. Eight experimental diets with four protein levels (30, 35, 40 and 45% P) and two lipid levels (4 and 12% L) were tested. Fecundity (FC), reproductive effort (RE), hatching rate (HT), Gonadosomatic Index (GSI), Hepatosomatic Index (HSI), and larval tests: starvation survival and tolerance to high salinity (45 psu), were evaluated. The results show that protein- ipid interactions have different effects on egg quality and larval stress tests. The diet with the highest mean in FC, RE and HT was P30L12, while the P30L4 diet obtained the lowest averages in these parameters. The GSI and HSI were independent of the dietary treatments and no differences were found whencomparing the two indexes. The present study showed that the P30L4 diet is not the best option for broodstock of the species and the P35L4 diet is recommended since it guarantees egg and larval quality similar to most of the diets evaluated.
Keywords: Feeding; Proteins; Prawns; Lipids; Boodstock